PENGARUH LOKASI DAN SARANA TRANSPORTASI TERHADAP DISTRIBUSI LOGISTIK DI WILAYAH KOARMADA III - Adam, Adam; Herbowo, Dono; Puliwarna, Tunggul (Program Studi Pendidikan Manajemen Perkantoran, 2021)
The delays and constraints that distribution centers have in supplying logistics that are often faced are related to transportation and transportation facilities that are not optimal, as well as the location of distribution centers to the remote Koarmada III area. In this study, an analysis of the effectiveness of the implementation of logistics distribution by a logistics distribution agency was carried out and the influence of the implementation of logistics distribution on supply performance to support the Koarmada III Marine Combat Operations. From the measurement model obtained using SEM AMOS software on the three variables of Location, Transportation and Inventory that builds Logistic Distribution, Location variable has a high value of 0.566. This means that the effectiveness of the implementation of logistics distribution in distributing logistics supplies from the distribution center to Koarmada III is not effective. So that in order to answer the existing problems, the Indonesian Navy needs to plan the formation of a logistics supply distribution organization through organizational validation, building reserve locations that are in strategic positions, building infrastructure and managing logistics supplies in a comprehensive and integrated manner.Keywords : Distribution Logistic; Effectivity; Location; Transportation